The path made clear [compact disc, unabridged] : discovering your life's direction and purpose - Winfrey, Oprah (Macmillan Audiobook, 2019)
In her latest book, Oprah shares what she sees as a guide for listeners activating their deepest vision of themselves, offering the framework for creating not just a life of success, but one of significance. The ten chapters are organized to help listeners recognize the important milestones along the road to self-discovery, laying out what they really need in order to achieve personal contentment, and what life's detours are there to teach.